2016
DOI: 10.1017/s1368980016002573
|View full text |Cite
|
Sign up to set email alerts
|

The climatic impact of food consumption in a representative sample of Irish adults and implications for food and nutrition policy

Abstract: To evaluate the greenhouse gas emissions (GHGE) associated with the diet of Irish adults. GHGE were estimated by applying conversion factors to habitual food consumption data taken from the National Adult Nutrition Survey, which was representative of the population. Descriptive analyses were undertaken for GHGE for the total population, as well as accounting for energy misreporting and across categories of sociodemographic and socio-economic factors and tertiles of emissions. Republic of Ireland. Adults aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
36
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 78 publications
12
36
1
3
Order By: Relevance
“…Extensive detail on the methodology used to derive GHGE, and the aggregation of food groups has been previously described by Hyland et al . (). All foods consumed were assigned to one of sixty‐seven food groups.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Extensive detail on the methodology used to derive GHGE, and the aggregation of food groups has been previously described by Hyland et al . (). All foods consumed were assigned to one of sixty‐seven food groups.…”
Section: Methodsmentioning
confidence: 97%
“…Previous research has shown the dietary carbon footprint of Irish adults to be 6.5 kg CO 2 eq day −1 (Hyland et al ., ). However, average daily dietary emissions do not reflect the diversity of GHGE patterns across a population.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…One study indicates that, despite the likelihood that more consumers of vegetarian diets will lead to reduced GHGEs, this outcome is not guaranteed. For instance, substituting cheese for chicken in a diet could result in higher aggregate GHGE production if the energy and nutrient content is not considered and production of the vegetarian substitute is associated with higher GHGEs [26]. Other important factors are transportation (especially long-distance), deep-freezing, and some specific horticultural practices, all of which can lead to higher environmental damage than locally produced organic meat [22].…”
Section: Ghge Impacts For Production Of Lov Dietsmentioning
confidence: 99%
“…Alguns estudos observaram que dietas com base em frutas e vegetais têm baixa emissão de GEE, assim como dietas ricas em itens com alto teor de açúcares (Hyland et al, 2016), e que, em alguns casos, o consumo de processados pode emitir menos GEE caso as frutas e vegetais tenham que ser produzidos em estufas, sejam exóticos, transportados entre locais distantes ou com necessidade de armazenamento por longos períodos após a colheita (Carlsson-Kanyama & Gonzalez, 2009;Hoolohan et al, 2013). Além de trocas na dieta visando menor emissão de GEE, devem ser objetivadas estratégias mais amplas no sentido de dietas sustentáveis.…”
Section: Discussionunclassified